Dietary resveratrol modulates rumen microbiota and metabolic function in Tibetan sheep: an integrated 16S rRNA sequencing and metabolomics analysis - Xie, Wenling; Zhang, Yu; Feng, Yuan; Li, Yujie; Gui, Linsheng; Hou, Shengzhen; Han, Lijuan; Yuan, Zhenzhen; Yang, Chao; Sun, Shengnan (Frontiers in Microbiology, 2025)
IntroductionResveratrol (RES), a natural plant polyphenolic compound, can be used as a dietary supplement and has shown good application after addition to monogastric animal diets, but fewer studies have been conducted in ruminants, especially in Tibetan sheep where no deeper studies have been made. In this study, we used 16S rRNA and metabolomics systems to investigate the effects of different doses of resveratrol added to the diets of Tibetan sheep on the microbial community structure and metabolomics of their rumen.ResultsThe results showed a significant (p < 0.05) increase in rumen papilla length in the H-RES group, along with elevated acetate and butyrate concentrations. Microbial analysis revealed significantly higher (p < 0.05) relative abundance of Firmicutes in the H-RES group, including the genera Prevotella and Ruminococcus. Metabolic pathway enrichment analysis revealed significant (p < 0.05) enrichment of amino acid metabolism-related pathways. In addition, specific microbial genera, Lactobacillus spp. and Ruminococcus spp. showed significant correlations with metabolites such as pantothenic acid and isoleucine, indicating differential regulatory effects.ConclusionIn summary, daily supplementation with 1.5 g of resveratrol (H-RES) improved rumen morphology and fermentation processes in Tibetan sheep. These improvements were closely related to changes in microbial community structure and metabolite interactions. The study of rumen microbial community structure and metabolite changes provides new ideas for regulating the rumen environment of Tibetan sheep.